Thermal impairment of reproduction is differentially expressed in maiden and repeat spawning Atlantic salmon - Pankhurst, NW; King, HR; Kelli Anderson; Elizur, A; Pankhurst, PM; Ruff, N (2011)
Groups of maiden or repeat spawning Atlantic salmon were maintained during vitellogenesis in austral autumn at either 14 °C or 22 °C through until April when all fish were transferred to a spawning temperature of 8 °C. There was no difference in body weight within groups for maidens and repeats, with repeats being consistently larger than maidens, no difference in condition factor amongst groups, but consistently higher gonad weight in repeats than maidens. Gonadosomatic index (GSI) and follicle diameter were suppressed in both maidens and repeats at 22 °C, with the effect being most marked in repeat spawners. Relative fecundity (egg kg −1 ) determined from ovarian tissue samples also showed depression in repeats at 22 °C. Fish from both age classes held at 22 °C had a higher proportion of atretic follicles. Plasma levels of estradiol-17β (E 2 ) were strongly depressed in both maidens and repeats exposed to 22 °C throughout autumn but there was some evidence of recovery amongst maiden fish by late April. A similar effect was seen on plasma testosterone (T) levels. Plasma cortisol levels were generally low and typical of levels in unstressed fish indicating that stress did not account for the inhibitory effects observed. Hepatic zona pellucida protein gene expression was significantly inhibited in both maiden and repeat spawning fish reared at 22 °C, but with some evidence of recovery after temperature reduction to 8 °C. Hepatic vitellogenin (Vtg) gene expression was also lower in both maiden and repeat spawning fish exposed to 22 °C and this was accompanied by reduced plasma Vtg levels in maidens, but not repeats at 22 °C. Maidens at 14 °C began ovulating first followed by repeats at 14 °C, then repeats at 22 °C followed by maidens at 22 °C. There was reduced fertility in maidens at 22 °C relative to both maidens and repeats at 14 °C, whereas repeats at 22 °C showed intermediate fertility between 14 °C fish and 22 °C maidens. Survival to the eyed egg stage was highest in maidens at 14 °C, significantly ...